THE RELATIONSHIP BETWEEN DURATION OF DIALYSIS AND HISTORY OF BLOOD TRANSFUSION WITH HEPATITIS C SEROPREVALENCE IN HEMODIALYSIS PATIENTS: A CROSS-SECTIONAL STUDY AT GADJAH MADA UNIVERSITY ACADEMIC HOSPITAL - Kurnia Fitriasari; Marsetyawan Heparis Nur Ekanda Soesatyo; Dewi Sulistyawati (Journal of Vocational Health Studies, 2025)
Background: Hepatitis C Virus (HCV) is an RNA virus that causes hepatitis C disease. Hemodialysis patients are a group at high risk of becoming infected with the HCV. Based on prior research, the duration of hemodialysis has been identified as an independent risk factor for HCV. Risk factors for HCV transmission in hemodialysis patients can also include blood transfusions. Purpose: This research aimed to determine the relationship between the duration of dialysis and the history of blood transfusion with HCV seroprevalence in hemodialysis patients at Gadjah Mada University Academic Hospital. Method: This research utilized a cross-sectional research design. The research data were based on secondary data from the medical records of hemodialysis patients at Gadjah Mada University Academic Hospital. Result: The results were analyzed descriptively and statistically using the Chi-square test with significance (α = 0.05). Data obtained from this research showed that the HCV seroprevalence of hemodialysis patients at Gadjah Mada University Academic Hospital is 20.5%. The test results revealed a relationship between duration of dialysis with HCV seroprevalence in hemodialysis patients is a p-value = 0.021 (p-value < α), and a relationship between history of blood transfusion with HCV seroprevalence in hemodialysis patients is a p-value = 0.024 (p-value < α). Conclusion: The results of the Chi-square test showed a relationship between duration of dialysis and history of blood transfusion with HCV seroprevalence in hemodialysis patients at Gadjah Mada University Academic Hospital.